Use of a Modified STROOP Test to Assess Color Discrimination Deficit in Parkinson's Disease - Langston, Rebekah G.; Virmani, Tuhin (Frontiers in Neurology, 2018)
Objective: To objectively measure color vision dysfunction in idiopathic Parkinson’s disease (iPD) using an easily administered, essentially free, modified Stroop test. Methods: 61 iPD patients and 26 age-matched controls (HC) were enrolled after IRB approval and performed congruent (CST) and incongruent (IST) modified Stroop tests consisting of 40 words in 10 colors arranged in a 5x8 grid. The scorer was blinded to participant diagnosis. Errors on IST were defined as type 1 (written word reported rather than color) or type 2 (color reported different from the written word or its color). Results: The iPD group and the control group completed testing with similar CST performance. On the IST, 75.4% of iPD patients had type 2 errors (p=0.001, OR 4.907, 95%CI 1.83813.097) compared to 38.5% HC, with a positive predictive value of 82%. The mean number of type 2 errors was also higher in the iPD group, even with MoCA scores as a covariate in the analysis. Type 1 errors were not significantly different between the groups. A univariate logistic regression model with age, gender, MoCA, normalized IST completion time and the presence/absence of type 2 errors also resulted in type 2 errors as the only significant factor in the equation (p=0.026). Conclusions: The modified Stroop test incorporated into the clinical evaluation of a patient may provide a quick and inexpensive objective measure of a non-motor feature of iPD, which could help in the clinical diagnosis of iPD in conjunction with the motor assessments currently used by neurologists.